The ethics of marginality : a new approach to gay studies - Champagne, John (University of Minnesota Press, 1995)
Is celebration of culturally marginalized people by the dominant culture actually benefitting those who are oppressed? Whose stakes are served in such a celebration, and how are existing power relations altered? These are some of the questions John Champagne asks in this original and timely critique, which moves gay studies beyond both identity politics and the ""rights"" discourse within which much of contemporary gay studies is positioned. Champagne argues that in the modern West, culturally marginalized people such as gays cannot define and legitimate their own existence outside the framewor.